The determinants of knowledge sharing among bank employees and its effect on bank services innovation - Ibrahim, Muhammad Bello (2020)
Knowledge sharing is a voluntary and mindful act of converting and exchanging knowledge, skills and experiences among employees and co-workers in an organization, or group or even between one organization and another. The main objective of this study is to understand and analyse the key factors determinants of knowledge sharing among bank employees, through the lens of negotiation, reciprocity, exchange characteristics, partner characteristics and communication frequency. At the same time, the research measured the impact of these variables on bank services innovation. Thus, the significance of negotiated and reciprocated cooperative behaviors among bank employees and co-workers in generating strong ties through social interaction and sharing of knowledge was investigated. Using these constructs the research proposed its framework. The research gap explores and explained these paradigms for determining knowledge sharing among bank employees, and enhanced their capacity for bank services innovation. Online data collection technique was used, 540 questionnaires were administered to senior staff of the 5 selected banks in Nigeria, via emails, short message service (SMS) and or WhatsApp chat message. The study achieved a response rate of 63%; 342 questionnaires were returned, out of these 298 were useable questionnaires. Partial least square structural equation modelling (PLS-SEM) was used to analyze the data. The findings revealed that all hypothesized relationships of the research model, except one were statistically significant and supported. The unique findings of this thesis aside achieving its set objectives, is linking its constructs in a mediated association with knowledge sharing to bank services innovation. This is against what obtained in most existing literatures reviewed, which shows the concept of knowledge sharing separate from innovation. The study further serves as a guide towards understanding the way employees of the Nigerian banking sector in particular, used the variables of our model to share knowledge, expertise, and experience in the current era of globalization supported by advanced information and self-help technologies. Internationally, the study has highlighted some valuable contributions of these key determinants of knowledge sharing and its effect on services innovation; and offer useful dissertation for practice to executive management of banks in particular, entrepreneurs, businesses and even public organizations. However, this study is limited by its scope, time and resources. Therefore, improvement is recommended both in context and theory.